On the Linear Convergence of PC-Method for a Class of Linear Variational Inequalities (Journal of Computational Mathematics, 1999)
This paper studies the linear convergence properties of a class of the projection and contraction methods for the affine variational inequalities, and proposes a necessary and sufficient condition under which PC-Method has a globally linear convergence rate.
Keywords: Affine variational inequality; Projection and contraction method; Linear convergence.